Psychological Impact of Infertility on Couples: A Cross-Sectional Study of Coping Strategies: Psychological Impact of Infertility on Couples - Yousaf, Munazza; Umer, Unzila; Raziq, Naila; Shinwari, Laila (Pakistan Journal of Health Sciences, 2026)
Infertility is not only a biomedical concern but also a source of considerable psychological stress for both partners, affecting emotional health and relationship functioning. The distinct emotional and coping processes of infertile couples necessitate understanding emotional distress for the planning of structured psychosocial support. Objective: To evaluate the psychological effect of infertility and find the coping mechanisms employed by infertile couples attending Maqsood Medical Complex and General Hospital, Peshawar. Methods: This cross-sectional descriptive study was carried out from April 1st, 2025, to September 30, 2025, on 130 infertile couples. Data were gathered on sociodemographic characteristics, the Hospital Anxiety and Depression Scale (HADS), and the Brief COPE inventory. The means ± SD were calculated for continuous variables, the frequencies were calculated for categorical variables, while the associations of coping strategies with psychological distress were handled using chi-square and Pearson correlation tests. Results: Of the 130 couples studied, 61.5% reported clinically significant anxiety and 49.2% reported depressive symptoms. Female partners consistently had higher mean scores for anxiety and depression than their male counterparts. Problem-focused coping (planning, active coping, and positive reframing) was related to lower levels of distress, while avoidant and emotion-focused coping were associated with higher anxiety and depression. Conclusions: Infertility carries a significant emotional burden, especially for women, and emotional coping strategies have a strong bearing on the psychological impact. It is critical that couple-focused psychosocial support and stress-management counseling be integrated into the psychosocial aspects of infertility care.